2018
DOI: 10.5194/amt-11-3373-2018
|View full text |Cite
|
Sign up to set email alerts
|

The Community Cloud retrieval for CLimate (CC4CL) – Part 1: A framework applied to multiple satellite imaging sensors

Abstract: Abstract. We present here the key features of the Community Cloud retrieval for CLimate (CC4CL) processing algorithm. We focus on the novel features of the framework: the optimal estimation approach in general, explicit uncertainty quantification through rigorous propagation of all known error sources into the final product, and the consistency of our long-term, multi-platform time series provided at various resolutions, from 0.5 to 0.02 • .By describing all key input data and processing steps, we aim to infor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…The retrieval system employed for cloud properties is the Community Cloud retrieval for CLimate (CC4CL), which is sum-10 marized in Stengel et al (2017) and described in detail in Sus et al (2018) and McGarragh et al (2018). However, further developments have taken place since v2, of which the key elements are listed in the following paragraphs.…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The retrieval system employed for cloud properties is the Community Cloud retrieval for CLimate (CC4CL), which is sum-10 marized in Stengel et al (2017) and described in detail in Sus et al (2018) and McGarragh et al (2018). However, further developments have taken place since v2, of which the key elements are listed in the following paragraphs.…”
Section: Algorithmsmentioning
confidence: 99%
“…More specifically, the CAL_LID_L2_05kmCLay-Prov product was downloaded from the ICARE Data and Service Center (http://www.icare.univ-lille1.fr). To investigate the sensitivity of passive imager retrievals to the thinnest cloud layers, the cloud optical depth profiles included in the CALIOP profiles were employed as in Karlsson and 5 Johansson (2013); Stengel et al (2013); Sus et al (2018). Following this approach different scenarios for excluding optically thin cloud layers are investigated when discussing validation of CMA, CPH and CTH below.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…For CTH and CPH the scores are also shown as a function of (COT th ), although (COT th ) is here referring to the optical thickness into the cloud (top-down) at which the reference value was taken from the CALIOP profile (SD = Standard deviation). are described by prognostic equations for cloud condensate and cloud fraction obeying mass balance equations (Tiedtke, 1993). Clouds are defined by the horizontal coverage of the grid box by cloud and the mass mixing ratio of total cloud condensate, along with the constraint that cloud air is saturated with regard to liquid water and ice.…”
Section: Era-interim Reanalysismentioning
confidence: 99%
“…Including additional thermal channels allows for the possibility of retrieving information on cloud transparency from which it is possible to separate the cloud from the below-cloud signal. In particular, the 3.7 µm channel paired with 11 µm has been used to retrieve cloud top pressure along with a single microphysical parameter that describes the cloud radiative thickness in the infrared, typically referred to as the "effective emissivity" (Szejwach, 1982;Wu, 1987;Liou et al, 1990;Ou et al, 1995). In a similar man-ner, have shown that the relative interdependence of optical thickness and effective radius in the 3.7 and 11.0 µm combination allows these to be retrieved along with cloud top pressure, although with a significantly greater uncertainty than using solar wavelengths during the day.…”
Section: Introductionmentioning
confidence: 99%